An Integrated Approach to the Prevention of Postpartum Bleeding in High-Risk Patients - D. A. Artymuk; S. V. Apresyan; N. V. Artymuk; T. Yu. Marochko; N. M. Shibelgut; N. A. Batina (Фундаментальная и клиническая медицина)
Aim. To evaluate the effectiveness of an integrated approach to the prevention of postpartum hemorrhage (PPH) in high-risk patients using uterine balloon tamponade with a double-balloon system, double-sided compression suture on the lower uterine segment, and administration of a uterotonic drug.Materials and Methods. Here we performed an open-label, comparative, controlled clinical trial aimed at establishing superiority. 144 pregnant patients with a high risk of PPH were randomised into 2 groups of 72 patients each. When implementing the study protocol, 22 patients were excluded from the treatment group, and 1 patient was excluded from the control group. In the treatment group, in addition to routine prevention, we applied an original technique which included uterine balloon tamponade with a double-balloon system, double-sided compression suture in the lower uterine segment, and intravenous administration of carbetocin. Control group received routine prevention of PPH. Statistical data analysis was carried out using Python version 3.11.Results. The volume of blood loss ranged from 500 to 1900 mL in the treatment group and from 400 to 3900 mL in the control group (p = 0.375). In the treatment group, the incidence of PPH was significantly lower than in the control group (10.00% and 49.30%, respectively, p < 0.0001), as well as the frequency of blood loss > 1000 mL (20.00% and 39.44%, respectively, p = 0.002). Blood loss > 2000 mL was recorded exclusively in the control group (12.69% patients). Among the secondary outcomes, blood products were used significantly less frequently in patients of the treatment group compared to the control group (12.00% and 29.58%, respectively, p = 0.027); hysterectomy was performed only in 6 (8.45%) patients of the control group. The duration of hospitalisation after childbirth did not differ significantly between the groups.Conclusion. An integrated approach to the prevention of PPH, which employs a double-sided compression suture on the lower uterine segment, uterine balloon tamponade using a double-balloon Zhukovsky system, and intravenous administration of a uterotonic drug, is more effective in preventing PPH in high-risk patients as compared with routine practice. Further multicenter extended studies in this direction are needed.